Adverse Events after Mass Azithromycin Treatments for Trachoma in Ethiopia - Ayele, Berhan (The American Society of Tropical Medicine and Hygiene, 2011)
During a cluster-randomized clinical trial for trachoma in Ethiopia, two rounds of adverse event surveillance were performed in a random sample of communities after community-wide mass azithromycin treatment. The prevalence of any reported adverse event ranged from 4.9% to 7.0% in children 1–9 years of age and from 17.0% to 18.7% in persons ≥ 10 years of age. Adverse events appeared to cluster by household and perhaps by village. Mass azithromycin distributions were well tolerated in this setting.